PERCEPTIONS OF HEALTH WORKERS TOWARDS THE AUTHORITY OF PHARMACISTS IN PRIMARY AND SECONDARY HEALTH CENTERS - Risyda Komaliya (Sean Institute, 2023)
The perception of the authority of pharmacists by health workers needs to be understood to increase understanding of the authority of pharmacists by other colleagues in primary health centers so that there is no overlap of authority and prevent conflicts that occur between health workers. This study was conducted to understand the perceptions of other health workers towards the authority of pharmacists in primary health centers in order to provide an understanding of what are the authority of pharmacists in the clinical field and management in primary and secondary health centers.